Pengaruh Working Capital Turnover dan Leverage terhadap Profitabilitas Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Tahun 2019-2024 - Yeni Haryani (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The impact of working capital turnover and leverage on the profitability of food and beverage companies listed on the Indonesia Stock Exchange between 2019 and 2024 is examined in this study. The primary topic of this study is the industry's profitability fluctuations, which point to variations in the effectiveness of financing choices and working capital management. This study aims to examine the partial and simultaneous effects of leverage and working capital turnover on business profitability. Using secondary data from the annual financial statements of five chosen companies, this study takes a quantitative approach, yielding 30 firm-year observations. Multiple linear regression was used with SPSS to evaluate the data. The findings show that working capital turnover significantly and negatively affects profitability, suggesting that overly high turnover may limit a company's capacity to produce optimal returns. Leverage, on the other hand, has a favorable and substantial impact on profitability, indicating that, when used wisely, debt can improve performance. Leverage and working capital turnover both have a big impact on profitability at the same time. These results highlight how crucial sensible financing techniques and balanced working capital management are to maintaining profitability in the food and beverage sector.